2014
DOI: 10.1103/physrevd.90.084028
|View full text |Cite
|
Sign up to set email alerts
|

Hamilton-Jacobi formalism for tachyon inflation

Abstract: Tachyon inflation is reconsidered by using the recent observational data obtained from Planck-2013 and BICEP2. The Hamilton-Jacobi formalism is picked out as a desirable approach in this work, which allows one to easily obtain the main parameters of the model. The Hubble parameter is supposed as a power-law and exponential function of the scalar field, and each case is considered separately. The constraints on the model, which come from observational data, are explained during the work. The results show a suit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Instead of the potential, in the formalism Hubble parameter is given as a function of the scalar field. This formalism in cold inflationary studies has got its place [26][27][28][29][30][31][32], however up to our knowledge there is no work considering warm inflation using this formalism. Then it sounds interesting to investigate warm inflation using this powerful formalism.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of the potential, in the formalism Hubble parameter is given as a function of the scalar field. This formalism in cold inflationary studies has got its place [26][27][28][29][30][31][32], however up to our knowledge there is no work considering warm inflation using this formalism. Then it sounds interesting to investigate warm inflation using this powerful formalism.…”
Section: Introductionmentioning
confidence: 99%
“…Effective potential for tachyon field in string theory were computed in reference [34]. Tachyon field were also considered in Hamilton-Jacobi approach [35] and in a logamediate inflationary model [36]. In ref.…”
Section: Introductionmentioning
confidence: 99%
“…Then, by considering the scalar perturbations it was shown that, in general, the amplitude of the scalar perturbation could be evolve even on superhorizon scales. The work has been improved in [39], where the authors use Hamilton-Jacobi formalism [40][41][42][43][44][45][46] and extract an exact solution for the model. It was determined that the solution confirms attractor behavior.…”
Section: Introductionmentioning
confidence: 99%